Female Religious Authority in Shi'i Islam: Past and Present: (by Mirjam Künkler and Devin J. Stewart, Eds.) (American Journal of Islam and Society, 2023)
Islamic religious authority is conventionally understood to be an exclusively male purview. Yet when dissected into its various manifestations – leading prayer, preaching, issuing fatwas, transmitting hadith, judging in court, teaching law, theology, and other Islamic sciences and, generally shaping the Islamic scholarly tradition – nuances emerge that hint at the presence of women in the performance of some of these functions. This collection of case studies, covering the period from classical Islam to the present, and taken from across the Twelver Shi‘i Islamic world, reflects on the roles that women have played in exercising religious authority across time and space. Comparative reflection on the case studies allows for the formulation of hypotheses regarding the conditions and developments – whether theological, jurisprudential, social, economic, or political – that enhanced or stifled the flourishing of female religious authority in Twelver Shi‘i Islam.